Assessing the Spatial Variation of Aerosol Optical Depth and its Relationship with Land Use/Land Cover in Kathmandu Valley, Nepal - Shrestha, Dibikshya; Chand, Aayush; Thapa, Prejika; Ojha, Bibek (Journal of Land Management and Geomatics Education, 2025)
Aerosols play a crucial role in influencing atmospheric processes, air quality, and human health. Understanding the relationship between land use/land cover (LULC) and aerosol optical depth (AOD) is essential for developing effective land management and air pollution mitigation strategies. This study investigates the spatial variation of AOD and its association with LULC in Kathmandu Valley, Nepal, during the summer season of 2023. MODIS AOD products and Landsat 8-derived indices, including the Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI), and Normalized Difference Water Index (NDWI), were utilized for this purpose. Spatial analysis revealed that lower AOD values were observed over forested areas, while higher concentrations were associated with water bodies, grasslands, and built-up areas. Correlation and regression analyses confirmed a negative relationship between vegetation cover and AOD, and a positive association between built-up areas, water surfaces and aerosol loading. The study highlights the significant influence of LULC on aerosol distribution and provides essential information for land management and air pollution mitigation strategies.